Application of the Inquiry Learning Model to Improve Student Learning Outcomes in the Subject of Islamic Religion and Moral Education in East Tanjung Jabung 9 Public Junior High School - Neni Indriyani, Erlina; Hindun, Hindun; Hayat, Najmul (International Journal of Advanced Multidisciplinary, 2023)
This study aims to examine student learning outcomes in applying the Inquiry Learning model to Islamic Religious Education Class VIII subjects at East Tanjung Jabung 9 Junior High School. This research is a qualitative research with a qualitative descriptive approach method. The low student learning outcomes for the lessons given by the teacher at school is an example that the completeness of learning outcomes has not reached the maximum point or has not been successful. This requires changes in teachers, especially in organizing classes, choosing appropriate teaching methods, teaching and learning strategies, as well as the attitudes and characteristics of teachers in managing the teaching and learning process in the classroom. The application of the Inquiry Learning model for Islamic Religious Education and Moral Education subjects at Tanjung Jabung Timur 9 Public Junior High School is effective in increasing student learning outcomes because it creates active interaction and participation not one way, students seek, find, ask questions, conclude. the learning activities use systematic steps of the Inquiry Learning method, namely a) Formulating problems, b) Submitting hypotheses, c) Collecting data, d) Testing hypotheses based on the data collected, f) Making conclusions.